325 THROMBOEMBOLISM IN MULTIPLE MYELOMA PATIENTS RECEIVING THALIDOMIDE COMBINATION CHEMOTHERAPY. Issue 1 (1st January 2007) - Wright, A.; Elkins, S.; Files, J.; Bigelow, C.; Herrin, V.; Sample, M.
Abstract : Purpose: To establish the incidence of thromboembolism (TBE) in multiple myeloma (MM) patients on thalidomide combination chemotherapy. Methods: A retrospective review was performed on all multiple myeloma patients at our tertiary care facility from January 2000 to December 2006. Patients were assessed for baseline characteristics, including age, sex, and past medical and surgical histories. Risk factors for TBE were evaluated, including a documented hypercoagulable state, a history of prior TBE, comorbidities, cytogenetics, and concurrent medications. It was also noted whether a central venous catheter (CVC) was in place. TBE included deep vein thromboses (DVTs) and pulmonary embolism (PE). It was also noted if patients had arterial TBEs. Patient chemotherapy regimens with or without thalidomide were reviewed, and each patient was assessed for evidence of TBE. Furthermore, thalidomide doses and titration intervals were documented. If thalidomide was used, patients were evaluated for concurrent use of prophylactic anticoagulation. Types of anticoagulation included low-molecular-weight heparin, full-dose warfarin, low-dose warfarin (usually 1 mg), and aspirin. If the patient had documented TBE, the median time to TBE while on the thalidomide combination was noted. Patients on full anticoagulation following TBE were followed for continued thalidomide use and bleeding events. Results: Of 118 eligible patients, there were 29 (24% of patients) occurrences of DVT or PE. Preliminary results show that 13 (11%) of the patients with TBE were on some thalidomide combination, whereas 15 (13%) were not. Seven of 13 patients with TBE on thalidomide were not on prophylactic anticoagulation. Three events occurred on low-dose warfarin, two on full-dose warfarin, and one on enoxaparin. Conclusions: It has been previously reported that about 10% of MM patients develop DVT when treated with chemotherapy alone. DVT rates of 25 to 30% have been documented with the addition of thalidomide to conventional chemotherapy or dexamethasone, whereas it occurs in only 3% of those treated with dexamethasone alone. No randomized trials have been done to establish the most effective type of prophylactic anticoagulation in this patient population. We hope to identify those patients at highest risk for TBE in our population and the best regimen for TBE prophylaxis.